Application of Classical and Genomic Cryptography on Textual Dataset - İbrahim Türkoğlu; Alev Kaya (Sakarya University Journal of Computer and Information Sciences)
Cryptology is one of the methods used when sharing confidential or private data over any communication network that poses a security risk. It is applied to restrict access, minimize or completely prevent dangerous situations. Cryptographic algorithms use a combination of mathematical operations and applications to protect information. It strives to ensure the confidentiality, integrity, availability and non-repudiation of information. In other words, it aims to keep data safe against all kinds of threats. However, the performance of these objectives depends on various factors. These factors include the file format used, the volume and complexity of the data. Additionally, the key system and application platform (software and hardware) also affect performance. These variables determine the effectiveness of cryptographic algorithms. In fact, existing cryptographic algorithms may be inadequate or ineffective in the face of new requirements. Therefore, new techniques need to be designed to meet such needs. This study, one of the new generation cryptographic techniques, includes a symmetric key genomics (DNA)-based application. The aim is to test the suitability of genomic encryption on artificial data sets (100 and 500 KB, 1 and 5 MB) generated from the content named "Siyasetname" in the Turkish textual data type. The usability of the genomic encryption technique, which has not been applied before in Turkish data sets, was tested by comparing it with classical algorithms such as AES (symmetric) and ECDH (asymmetric). Performance criteria are determined as encoding and decoding times (seconds), memory consumption (MB) and processor usage (%), which are accepted in the literature for textual data type. It is supported by different indicators according to dimensions and more successful outcomes compared to similar studies in the literature. These findings suggest that DNA/genomic encryption techniques can be considered as an alternative solution to cryptographic requirements.